Combine therapy as a modern approach to treatment of allergic rhinitis - Alexander V. Emelyanov ("Consilium Medicum" Publishing house, 2021)
Allergic rhinitis (AR) is one the most common allergic diseases affecting from 10 to 40% of the population in different countries, including Russia. AR is a risk factor of bronchial asthma, other upper airway disease and may decrease patient quality of life, their productivity, increase probability of occupational traumatism, depression and anxiety. AR also presents a substantial economic burden. The rationale to use fixed dose combination of intranasal steroids and topical H1 antihistamines includes suboptimal control of symptoms by monotherapy, its complementary pharmacologic activity and the results of clinical trials. This review focused on fixed dose combination of intranasal mometasone furoate and olopataine. Double blind placebo-controlled and open clinical trials have confirmed that this combination decreased severity of nasal and ocular symptoms of seasonal and perennial AR, improved patient quality of life and had a good tolerability. Its efficacy was higher than those of monotherapy. Fast onset of action and sustainable effect on symptoms (during 1 yr) may improve adherence patients to the treatment and control of symptoms of AR.